Climate-smart agriculture measurement, reporting and verification in the Republic of Zambia - World Agroforestry Centre; Unique Forestry and Land Use (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2019)
Although agriculture accounts for only 8.2% of the Republic of Zambia’s gross domestic product (GDP), almost half of the country’s economically active popula- tion works in the sector. Climate change poses a grave risk to the growth and sustainability of Zambian agricul- ture. Since 1960 average temperatures have increased 1.3° C, and average rainfall has decreased 1.9 mm/month in main agricultural regions, while increasing in other areas.